Pengabdian Kepada Masyarakat Melalui Peningkatan Minat Belajar Mengaji Al-Qur’an Anak Usia Dini - Lilis Aliyatuz Zahroh; Eli Masnawati; Cilda Thesisa Ilmawan Dzinnur; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan; Tri Marfiyanto; Solchan Ghozali (Lembaga Pengembangan Kinerja Dosen, 2024)
The urgency of the current generation is that it is necessary to improve the character of children so that they are ready to become young people who are ready to build the nation. Improving character requires strong education, especially in religious education, one of which is reciting the Koran. The aim of this service research is to increase interest in reading in young children. This service is described qualitatively using observational and documented data collection along with a qualitative descriptive approach. Data analysis is carried out by collecting, presenting, condensing and drawing conclusions from the data. The results of this service show that there is a need for strategies to increase interest in studying the Koran in young children. Children are instructed by the author to read, understand and apply the contents of the Koran in their daily lives.